#### Answer

C) 30

#### Work Step by Step

$y=6$
$.25x+.67y=.33(x+y)$
$.25x+.67y=.33(x+y)$
$.25x+.67*6=.33(x+6)$
$.25x+4 = .33x+2$
$.25x+4-.25x-2 = .33x+2-.25x-2$
$2 = 1/12*x$
$2*12 = 1/12*x*12$
$24 = x$

Published by
Prentice Hall

ISBN 10:
0133500403

ISBN 13:
978-0-13350-040-0

C) 30

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.